Versatile physiological functions of the Nudix hydrolase family in berry development and stress response in grapevine - Pei-pei WANG; Zhao-ke WANG; Le GUAN; Muhammad Salman HAIDER; Maazullah NASIM; Yong-bing YUAN; Geng-sen LIU; Xiang-peng LENG (Journal of Integrative Agriculture, 2022)
Nudix hydrolases are widely distributed across all classes of organisms and provide the potential capacity to hydrolyze a wide range of organic pyrophosphates. Although Nudix hydrolases are involved in plant detoxification processes in response to abiotic and biotic stresses, the biological functions of Nudix hydrolases remain largely unclear in grapevine. In the present study, a total of 25 putative grapevine Nudix hydrolases (VvNUDXs) were identified by bioinformatics analysis and classified into eight subfamilies based to their preferred substrates. Both tandem and segmental duplications were responsible for the evolution and expansion of the NUDX gene family in grapevine. To investigate the regulatory roles of VvNUDX genes during growth and development, as well as in response to abiotic and biotic stresses in grapevine, the expression patterns were revealed in publicly available microarray data. The spatial and temporal expression patterns of the VvNUDX genes indicated that they might play important roles in multiple developmental processes. Transcriptome and qRT-PCR analyses showed that ten VvNUDX genes were specifically expressed in grapevine berries, suggesting potential roles in grapevine berry development. Expression and phylogenetic analyses demonstrated that VvNUDX1 and VvNUDX3 might be involved in terpenoid biosynthesis in grapevine. Furthermore, most VvNUDX genes active toward the ADP-ribose/NADH showed different patterns in response to various abiotic and biotic stresses, such as salinity and drought, as well as different types of biotic treatments, such as Erysiphe necator, Bois Noir phytoplasma and leaf-roll-associated virus-3 (GLRaV-3). These results indicated that VvNUDX genes were associated with plant detoxification processes in response to abiotic and biotic stresses, and regulate the disease immunity and resistance pathways. The information obtained here may provide good opportunities to explore the physiological functions of VvNUDX genes in berry development and stress response networks in grapevine.